Poly-l-lysine-caused cell adhesion induces pyroptosis in THP-1 monocytes - Yu Chaoping; Zhao Wei; Duan Chujun; Xie Jiangang; Yin Wen (Open Life Sciences, 2022)
Pyroptosis is a kind of cell necrosis mediated by inflammasomes. The caspase 1-induced cleavage of gasdermin D (GSDMD) is a canonical pathway to cause membrane pores and eventually cell pyroptosis. Poly-l-lysine (PLL) is widely used to enhance cell adhesion during experiments. Human THP-1 cells are a typical cell line used to study pyroptosis due to their monocytic and macrophage-like characteristics. However, it was found that THP-1 cells seeded on the PLL-coated slides died. To figure out the reason, we observed the morphology of THP-1 cells on PLL-coated slides, which showed obvious pore forming on the cell membranes and cell swelling. The indicated pyroptosis-related protein expression was evaluated and it showed that the conventional caspase-1 pathway of pyroptosis was activated through the NLRP3 inflammasome in THP-1 monocytes on the PLL-coated slides. Hence, PLL-guided cell adhesion induces cell pyroptosis in THP-1 monocytes, which calls for THP-1 dominant studies of pyroptosis to avoid the use of PLL-coated slides or PLL-related drugs.